Combined Effects of HLA-B*57/5801 Elite Suppressor CD8+ T Cells and NK Cells on HIV-1 Replication - May, Megan E.; Pohlmeyer, Christopher W.; Kwaa, Abena K.; Mankowski, Madeleine C.; Bailey, Justin R.; Blankson, Joel N. (Frontiers in Cellular and Infection Microbiology, 2020)
Elite controllers or suppressors (ES) are HIV-1 infected individuals who maintain undetectable viral loads without anti-retroviral therapy. The HLA-B*57 allele is overrepresented in ES suggesting a role for HIV-specific CD8+ T cells in immune control. Natural killer (NK) cells also play a role in controlling viral replication, and genetic studies demonstrate that specific combinations of killer cell immunoglobulin-like receptor (KIR) alleles and HLA subtypes including HLA-B*57 correlate with delayed progression to AIDS. While prior studies have shown that both HIV-specific CD8+ T cells and NK cells can inhibit viral replication in vitro, the interaction between these two effector cells has not been studied. We performed in vitro suppression assays using CD8+ T cells and NK cells from HLA-B*57 ES either alone or in combination with each other. We found no evidence of antagonism or synergy between the CD8+ T cells and NK cells, suggesting that they have independent mechanisms of inhibition in vitro. Our data has implications for combined immunotherapy with CD8+ T cells and NK cells in HIV cure strategies.